Expanding and Improving Upper Primary Education in India - World Bank (Washington, DC, 2013)
This report considers the current status of upper primary school education in India. It looks at future impacts and recognizes the national level focus on elementary education. The importance of specific contexts in defining how states fulfill their constitutional responsibilities in upper primary education are studied. The report is based upon two studies whose findings include: length, structure & organization vary across and within states; the transition rate between primary and upper primary is high; transition rates and enrollment are lower for girls; school place is provided for current, but not future, demand; private unaided school enrollment is increasing; state qualification policies for teachers are not always relevant to instruction needs; in-service teacher training is very limited; discontinuity exists for curricula and subject weight between primary and upper primary schools; information overloads exist in syllabi, textbooks, and classroom processes; upper primary grades are cheaper when combined within an elementary school; a constitutional requirement for decentralized educational management exists; and expenditures need to increase before universalization of elementary education. Specific recommendations are given. Expansion and improvement of upper primary schooling, as endorsed by the Supreme Court of the Constitution's reference to the provision of education up to 14 years of age, will require both resources and reform.